2014
DOI: 10.1177/1461444814549041
|View full text |Cite
|
Sign up to set email alerts
|

The extent and nature of ideological selective exposure online: Combining survey responses with actual web log data from the 2013 Israeli Elections

Abstract: Do users tend to consume only like-minded political information online? We point to two problems with the existing knowledge about this debate. First, the measurement of media preferences by the typical means of surveys is less reliable than behavioral data. Second, most studies have analyzed only the extent of online exposure to like-minded content, not the users’ complete web-browsing repertoire. This study used both survey data and real-life browsing behavior (661,483 URLs from 15,976 websites visited by 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 37 publications
1
70
0
Order By: Relevance
“…Specifically, the effectiveness of providing population averages as anchors for duration measures should be studied. Applying multi-method approaches instead of relying on survey data only is another way to enhance the possibilities of survey and tracking data also allowing to directly asses response inaccuracies (e.g., Dvir-Gvirsman, Tsfati, & Menchen-Trevino, 2016).…”
Section: Recommendationsmentioning
confidence: 99%
“…Specifically, the effectiveness of providing population averages as anchors for duration measures should be studied. Applying multi-method approaches instead of relying on survey data only is another way to enhance the possibilities of survey and tracking data also allowing to directly asses response inaccuracies (e.g., Dvir-Gvirsman, Tsfati, & Menchen-Trevino, 2016).…”
Section: Recommendationsmentioning
confidence: 99%
“…For obvious reasons, this presents formidable methodological challengestracking one person's complete media intake over time is difficult enough, and most researchers would want to track multiple individuals. To my knowledge, no study has yet been able to accomplish this in a rigorous way, although Dvir-Gvirsman et al (2016) come the closest for online content sources. Consequently, much of the research that purports to examine personalized information environments analyzes only one platform or medium.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Most empirical work on the topic suggests that neither of these assumptions generally hold. Instead, people tend to exhibit moderate to strong preferences for ideologically-consistent content while failing to routinely reject content from the other side (Bakshy, Messing, & Adamic, 2015;Barberá, Jost, Nagler, Tucker, & Bonneau, 2015;Dvir-Gvirsman, Tsfati, & Menchen-Trevino, 2016;Garrett, 2009;Gentzkow & Shapiro, 2011;Hanna et al, 2013;Hargittai, Gallo, & Kane, 2008;Kobayashi & Ikeda, 2009). Some studies have found differences in the degrees of ideological self-segregation between liberals and conservatives (Barberá et al, 2015;Boutyline & Willer, 2017;Hanna et al, 2013) as well as between political issues (Bakshy et al, 2015;Barberá et al, 2015;Himelboim, McCreery, & Smith, 2013).…”
Section: Do Echo Chambers Exist?mentioning
confidence: 99%
“…This may seem like an un-controversial topic, particularly in the Trump era. However, there have been decades-long controversies about the extent and nature of selective exposure (Feldman, Stroud, Bimber, & Wojcieszak, 2013;Dvir-Gvirsman, Tsfati, & Menchen-Trevino, 2014;Hart et al, 2009;Sears & Freedman, 1967).…”
Section: Trace Partnership: Collecting Real-world Behaviors and Self mentioning
confidence: 99%